Pengaruh Kualitas Produk dan Desain Produk Terhadap Keputusan Pembelian Honda Scoopy F1 di Kediri - Lilik Maslikha (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
Product quality is the ability possessed by a product to be used within a certain period. Product design is the thing that adheres to the product that can be felt directly by consumers. Purchasing decision is an action or decision taken according to various considerations that have been made. This study aims to determine the effect of product quality and product design on purchasing decisions. The population in this study are consumers who buy and use Honda Scoopy, and the sample is 30 respondents. The design of this study uses quantitative methods by distributing questionnaires to respondents who are deemed worthy of being a source of data. Technical analysis in this study uses multiple linear regression. The results of this study indicate that product quality has a positive effect on purchasing decisions, product design has a positive effect on purchasing decisions, so product quality and product design variables are equally influential on purchasing decisions.